DIAGNÓSTICO SOBRE A UTILIZAÇÃO DE TÉCNICAS SUSTENTÁVEIS DURANTE O CICLO DE VIDA DE PROJETOS: UMA SURVEY NO NORTE FLUMINENSE COM FOCO NA INDÚSTRIA DE ÓLEO E GÁS. - Dias, Danyel Sousa (2013)
This work proposes to review the issues associated to sustainability and its correlation with the decision-making process of the Project Manager The target is to identify how issues related to the economy society and environment can affect the decisions of the Project Manager Currently both the Project Management and Sustainability are topics deeply discussed and analyzed by companies and professionals seeking the best way to reconcile them With the use of literature search seeking examples and concepts in Brazilian literature and abroad sought to gather the information necessary to create a set of information that would explain somehow how to present the main topics discussed to the academic and the major organizational public Later with the application of a survey through specific questionnaire developed to gather answers to the questions that form the set of points listed for the achievement of the main objective of this work is intended to achieve a qualitative analysis that points to the relevance of sustainable technics in decision-making of the Project Manager The field research will be limited to the Oil and Gas market the environs of the largest and main hub of E&P in Brazil today